Magnetized Bioconvective micropolar nanofluid flow over a wedge in the presence of oxytactic microorganisms - Patil, P.M.; Goudar, Bharath; Momoniat, E. (Case studies in thermal engineering, 2023)
The current study focuses on how a magnetic field and oxytactic microorganisms influence the flow of a micropolar nanofluid around a wedge in a bioconvective field. It has practical implications in numerous industries and fields, including oil and gas, aircraft, biological waste processing, bio-microsystems etc. We begin the analysis by transforming the dimensionality of the governing equations via non-similar transformations. The obtained equations are linearized using the Quasilinearization method before being discretized using the implicit finite difference approach. The literature study reveals that the earlier studies on wedge are restricted to only similarity solutions rather than non-similarity without the impact of oxytactic microorganisms. This study concentrates on the effect of oxytactic microorganisms in the nonlinear mixed convective micropolar nanofluid flow around a wedge. The Micropolar fluid reduces the velocity while increasing friction between the surrounding fluid and the wedge's wall. The greater Peclet and microbial density difference ratio values blunted the effects of the rise in microorganisms on the density profile changes. The growth in the oxytactic microbial parameter Δ1 improves the microorganism's mass transfer rate(Rex−1/2NSh). Specifically, a rise of approximately 21% is seen in Rex−1/2NSh in the presence of oxytactic microbes as compared to their absence at ξ=2 and Le=10. The microrotation parameter boosts the entropy for enhancing values of the Brinkman number. And the entropy is almost the same for the Newtonian and micropolar fluid cases for Br=0.1.